Influence of sediment additions on the mechanical behavior of fiber-reinforced concrete in aggressive environments - Goudih, Louafi; Sellaf, Hamid; Balegh, Benamar; Meksi, Ali; Hadj Mostefa, Adda; Dahamni, Mohamed Elamine (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The use of supplementary cementitious materials (SCM) in construction has gained popularity due to their ability to improve  the mechanical properties and environmental sustainability of concrete. This study aimed to investigate the potential of utilizing waste materials, specifically marble powder (MP) and dam sediment (DS), as partial replacements for cement in self-compacting concrete (SCC). The primary objectives were to recycle these waste materials and assess the durability and strength of SCC exposed to aggressive chemical environments.Methods: In this study, cement was partially replaced with 40% MP, 40% DS, and a combination of 20% MP and 20% DS. The performance of such concrete was evaluated through compressive strength tests conducted for 28 days. Durability was assessed by exposing the concrete to chemical attacks from hydrochloric acid (HCl), sulfuric acid (H₂SO₄), and sodium sulfate (Na₂SO₄) solutions. Mass loss due to these chemical attacks was also measured.Results: The concrete incorporating MP demonstrated compressive strengths similar to that of the control concrete, achieving 37.61 MPa at 28 days. The concrete with DS exhibited lower strength (31.81 MPa) and showed higher resistance to HCl (ML = 38.78%) compared to the MP concrete (ML = 40.74%). Additionally, all concrete samples exhibited good resistance to sulfuric acid due to the formation of expansive ettringite which protected the concrete from further degradation.Conclusions: The results indicated that both marble powder and dam sediment are viable supplementary materials for improving the mechanical properties and durability of SCC. The concrete with marble powder showed superior strength, while dam sediment contributed to enhanced acid resistance. The combination of these materials offers a sustainable solution for concrete exposed to aggressive environments.
Keywords: concrete (SCC); sediment; marble powder; fiber; mass loss; mechanical; aggressive environment